Dihydrosanguinarine enhances tryptophan metabolism and intestinal immune function via AhR pathway activation in broilers - Yue Su; Miaomiao Wang; Zhiyong Wu; Peng Huang; Jianguo Zeng (Journal of Animal Science and Biotechnology)
Abstract Background Tryptophan is essential for nutrition, immunity and neural activity, but cannot be synthesized endogenously. Certain natural products influence host health by modulating the gut microbiota to promote the production of tryptophan metabolites. Sanguinarine (SAN) enhances broiler immunity, however, its low bioavailability and underlying mechanisms remain unclear. This study aimed to decode the mechanisms by which sanguinarine enhances intestinal immune function in broilers. Methods Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was employed to identify the main metabolites of sanguinarine in the intestine. Subsequently, equal concentrations of sanguinarine and its metabolites were separately added to the diets. The effects of sanguinarine and its metabolites on the intestinal immune function of broiler chickens were evaluated using 16S rRNA gene amplicon sequencing and tryptophan metabolomics approaches. Results We determined that dihydrosanguinarine (DHSA) is the main metabolite of sanguinarine in the intestine. Both compounds increased average daily gain and reduced feed efficiency, thereby improving growth performance. They also enhanced ileal villus height and the villus-to-crypt (V/C) ratio while decreasing crypt depth and upregulating the mRNA expression of tight junction proteins ZO-1, occludin and claudin-1. Furthermore, both compounds promoted the proliferation of intestinal Lactobacillus species, a tryptophan-metabolizing bacterium, stimulated short-chain fatty acid production, and lowered intestinal pH. They regulated tryptophan metabolism by increasing the diversity and content of indole tryptophan metabolites, activating the aryl hydrocarbon receptor (AhR) pathway, and elevating the mRNA levels of CYP1A1, CYP1B1, SLC3A1, IDO2 and TPH1. Inflammatory cytokines IL-1β and IL-6 were inhibited, while anti-inflammatory cytokines IL-10 and IL-22, serum SIgA concentration, and intestinal MUC2 expression were increased. Notably, DHSA exhibited a more pronounced effect on enhancing immune function compared to SAN. Conclusions SAN is converted to DHSA in vivo, which increases its bioavailability. DHSA regulates tryptophan metabolism by activating the AhR pathway and modulating immune-related factors through changes in the gut microbiota. Notably, DHSA significantly increases the abundance of Lactobacillus, a key tryptophan-metabolizing bacterium, thereby enhancing intestinal immune function and improving broiler growth performance.